[OP.6B.06] SIMULTANEOUS MEASUREMENT OF ALDOSTERONE AND RENIN CONCENTRATIONS IN TEN MINUTES COULD CHANGE THE CLINICAL ASSESSMENT OF HYPERTENSIVE PATIENTS. (September 2017) - Satoh, F.; Morimoto, R.; Ono, Y.; Tezuka, Y.; Omata, K.; Nezu, M.; Iwakura, Y.; Igarashi, Y.; Kudo, M.; Gomez-sanchez, C.E.; Ito, S.
Abstract : Objective: The measurement of plasma aldosterone (PAC) and renin concentration (ARC) or activity (PRA) is useful for selecting antihypertensive agents as well as diagnosing primary aldosteronism (PA) in hypertensive patients. However, it takes several days to get results when measured by radioimmunoassay and development of more rapid assay has been long expected. In the present study, we characterized recently developed fully-automated chemiluminescent enzyme immunoassay (CLEIA) for PAC and ARC, which can be measured simultaneously in 10 minutes and 20 seconds, and clinical validation of their diagnostic abilities for detecting PA patients from hypertensive patients was also performed in this study. Design and method: We performed clinical validation of diagnostic ability of this newly developed assay-based screening of 125 patients with primary aldosteronism (75 aldosteronoma (APA) and 50 bilateral hyperplasia (BHA)) from 97 patients with essential hypertension (EH).The newly developed assays of both PAC and ARC adopted antibody-immobilized magnetic particles, called MAGRAPID with abilities of quick aggregations and dispersions. Results: Results of this novel measurements were significantly correlated with both radioimmunoassay measurements (PAC, ARC and PRA) and liquid chromatography-tandem mass spectrometry measurements (PAC). The analytical sensitivity of this particular novel ARC measurement was 0.1 pg/mL, which was better than that of radioimmunoassay (2.0 pg/mL). The ARC values measured by CLEIA were below than 2.0 pg/mL in 28.8% of all patients (52.0%, 44.0% and 3.1% in those with unilateral APA, BHA and EH, respectively). Using Bland-Altman plot analysis with the mass-spectrometry measurement, both bias and limits of agreement with 95% confidence interval of the automated PAC assay were smaller than those of the radioimmunoassay, indicating smaller systemic errors in the novel measurement. The ratio of PAC-over-ARC of 11.2 (ng/dL per pg/mL) provided 80.8% sensitivity and 94.9% specificity as a cut-off for differentiating primary aldosteronism from essential hypertension. Conclusions: This novel measurement is expected to be clinically reliable alternatives for conventional radioimmunoassay and to provide better throughput and cost-effectiveness in diagnosis of hyperaldosteronism from larger number of hypertensive patients in clinical settings.